THE SOUNDNESS LEVEL ASSESSMENT OF PT BANK PAN INDONESIA TBK USING RISK-BASED BANK RATING IN 2018-2022 - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2024)
The financial industry is crucial for a nation's growth and well-being, with banks playing a vital role in utilizing financial resources. The soundness of a bank is essential, with stakeholders including shareholders, bank management, customers, and the general public involved. Maintaining soundness is paramount for financial institutions like banks, as internal risk can affect the bank's financial status. This study examines the financial report of PT Bank Pan Indonesia Tbk for 2018-2022. The research uses historical data and descriptive data analysis methodology, analyzing financial statements using the Risk-Based Bank Rating method. This study indicates that PaninBank's soundness level is in a Very Healthy condition from 2018 to 2022, as measured by the NPL ratio, Good Corporate Governance, ROA ratio, NIM ratio, BOPO ratio, and CAR ratio. The soundness level of the PaninBank is also in a Very Healthy condition, with composite scores of 93%, 93%, 93%, 90%, and 93% for the five years spanning 2018-2022.